Expert opinion: Assessing cochlear implant candidacy and progress for people with English as an additional language. (1st April 2016) - Mahon, Merle; Rajput, Kaukab; Vickers, Debi
Abstract : Special considerations relating to cochlear implants (CIs) are necessary for deaf people for whom English is an additional language (EAL). The audiological and pre-linguistic skills criteria for CI candidacy are the same for children with EAL as for children from English-speaking families. However, thorough assessment is not straightforward, for example, requiring employment of experienced interpreters. To ensure family engagement and thus appropriate support in the home, clear understanding of the family's social and cultural framework and of their needs and requirements is essential. Equally, the family must be enabled to understand the implications of CI. Additional training of staff in CI teams may be needed. This article will address these and other issues for children and also consider the situation for adults.